Immersive Virtual Reality and Virtual Embodiment for Pain Relief - Matamala-Gomez, Marta; Donegan, Tony; Bottiroli, Sara; Sandrini, Giorgio; Sanchez-Vives, Maria V.; Tassorelli, Cristina (Frontiers in Human Neuroscience, 2019)
A significant body of experimental evidence has demonstrated that it is possible to induce the illusion of ownership of a fake limb or even an entire fake body using multisensory correlations. Recently, immersive virtual reality has allowed users to experience the same sensations of ownership over a virtual body inside an immersive virtual environment, which in turn allows virtual reality users to have the feeling of being “embodied” in a virtual body. Using such virtual embodiment to manipulate body perception is starting to be extensively investigated and may have clinical implications for conditions that involve altered body image such as chronic pain. Here, we review experimental and clinical studies that have explored the manipulation of an embodied virtual body in immersive virtual reality for both experimental and clinical pain relief. We discuss the current state of the art, as well as the challenges faced by, and ideas for, future research. Finally, we explore the potentialities of using an embodied virtual body in immersive virtual reality in the field of neurorehabilitation, specifically in the field of pain.